ASPEK FINANSIAL PENDIDIKAN ISLAM - Panggabean, Hadi Saputra (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
Education is a place to form a generation that has superior human resources. Through education a person will experience a process of maturity of attitudes, knowledge and skills. Therefore, the quality of education really determines the quality of a nation. It must be understood together that in the case of the operation of an education, it certainly cannot be separated from funding and managing funds. Advanced education is usually directly proportional to the amount of funding available. If funding an education is sufficient, it can be ensured that superior programs and policies will be realized, but conversely if an education experiences financial constraints, it is almost certainly not able to give birth to innovative policies.Nationally the country has designed a budget for education by 20 percent. A very large number of course. However, this large amount is not sufficient to finance all aspects of education, both public and private. Therefore, every education is required to be able to be independent in financial matters. Educational institutions are expected to be able to establish cooperation with the community and various parties who are then expected to be able to help empower education. Many ways that can be done by educational institutions in terms of raising education funds, including by collecting funds (fundraising) to educational partners or generous donors. In the context of Islamic education, for example, education fundraising strategies can also be carried out by optimizing Islamic philanthropy through the use of zakat, infaq, shadaqah, and waqf funds. With that, in writing this paper, the author will explore thoroughly the Financial Aspects of Islamic Education, while expecting constructive input and criticism, for the perfection of this paper.